2010
DOI: 10.1017/s1049023x00008529
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Showering Protocols for Mass-Casualty Decontamination

Abstract: A well-established provision for mass-casualty decontamination that incorporates the use of mobile showering units has been developed in the UK. The effectiveness of such decontamination procedures will be critical in minimizing or preventing the contamination of emergency responders and hospital infrastructure. The purpose of this study was to evaluate three empirical strategies designed to optimize existing decontamination procedures: (1) instructions in the form of a pictorial aid prior to decontamination; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…Half of respondents reported that shower duration would be between 30 and 60 seconds, below the recommended shower duration of 60 to 90 seconds identified in controlled studies of emergency decontamination. 13,14 Only a quarter of respondents reported that they would provide instructions to casualties about how to progress through the decontamination process. Where details of specific instructions were given, these included asking participants to walk slowly through the decontamination corridor, turn occasionally, and extend arms; these instructions were therefore broadly in line with current guidance, based on perceived best practice.…”
Section: Decontamination Showering Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Half of respondents reported that shower duration would be between 30 and 60 seconds, below the recommended shower duration of 60 to 90 seconds identified in controlled studies of emergency decontamination. 13,14 Only a quarter of respondents reported that they would provide instructions to casualties about how to progress through the decontamination process. Where details of specific instructions were given, these included asking participants to walk slowly through the decontamination corridor, turn occasionally, and extend arms; these instructions were therefore broadly in line with current guidance, based on perceived best practice.…”
Section: Decontamination Showering Processmentioning
confidence: 99%
“…12 However, POWER ET AL research into the effectiveness of showering in mass decontamination units suggests that active washing will be important. 14 …”
Section: Decontamination Showering Processmentioning
confidence: 99%
See 1 more Smart Citation
“…While the MDU showering protocol for ambulant casualties has been well defined and evaluated (4,(7)(8)(9), the nonambulant equivalent ("clinical decontamination") has not been subjected to rigorous testing. Consequently, there is currently no evidence-based guidance for clinical decontamination.…”
Section: Introductionmentioning
confidence: 99%
“…Many different decontamination methods have been developed (4)(5)(6). The most common one for mass casualties is wet type decontamination using detergents (7,8).…”
mentioning
confidence: 99%